Graphene-based zoom metalens adaptive imaging system. (1st May 2023) - Zhang, Qingyuan; Wang, Xinyi; Liang, Yawei; Chen, Xiaogang; Shao, Yan; Zhang, Qiaozhen; Zhu, Chenxi; Ma, Shikai; Luo, Yang
Abstract: A definition adaptive imaging system based on graphene zoom metalens is proposed. It combines a tunable metalens and an image clarity detection algorithm. Compared with traditional imaging systems, the focus position of the metalens can be adjusted arbitrarily by changing the graphene chemical potential rather than the physical structure. Further, an edge detection algorithm is used to detect the image definition, and then judge whether the current focal length of the lens is appropriate. According to the predetermined strategy the system will automatically adjust the focus of the metalens until a satisfactory image is obtained.